Pengalaman Komunikasi Penyintas Gangguan Psikomatik Akibat Ketakutan terhadap Covid-19 di Masa Pandemi - Paraswati, Vellyana; Dida, Susanne; Hafiar, Hanny (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
Psychosomatic symptoms can range from mental symptoms such as stress to physical symptoms such as the appearance of complaints in the body which, when checked, show no dysfunction in any part of the body. This research aims to find out and understand the communication experiences of survivors of psychosomatic disorders due to fear of COVID-19 during the pandemic This research uses a qualitative approach with phenomenological methods. The research subjects consisted of 8 (eight) informants who were carried out by snowballing. Data collection was carried out by interviews, observation and documentation. The results of the first research revealed that the COVID-19 pandemic was interpreted personally as causing fear and giving rise to various kinds of anxiety that had an impact on a person's physical and mental health. So, it is necessary to take preventive measures so that this virus does not spread further. On the other hand, excessive anxiety that causes physical complaints can cause a person to experience psychosomatic disorders. Psychosomatic symptoms can range from mental symptoms such as stress to physical symptoms such as the appearance of complaints in the body which, when checked, show no dysfunction in that part of the body. The psychosomatics experienced by a person can become an obstacle for a person in communicating. Someone who experiences psychosomatic disorders that are so severe that they interfere with daily activities need treatment by visiting a professional, either a psychologist or psychiatrist. The final findings that researchers obtained from the effects after therapeutic communication that was established, survivors became aware of the importance of consulting with professional staff to obtain relief so that they could return to normal activities. From the results of the research, researchers concluded that the anxiety experienced by a person can weaken their immune system, causing physical illness. When anxiety has an impact on daily activities, people need to go to professionals to get treatment so that the impact does not get worse. Gejala psikosomatik dapat berupa gejala mental seperti stress hingga menimbulkan gejala fisik seperti munculnya keluhan ditubuh yang ketika dilakukan pengecekan tidak terdapat disfungsi pada bagian tubuh. Penelitian ini bertujuan untuk mengetahui dan memahami pengalaman komunikasi penyintas gangguan psikosomatik akibat ketakutan terhadap COVID-19 di masa pandemi. Penelitian ini menggunakan pendekatan kualitatif dengan metode fenomenologi. Subyek penelitian terdiri atas 8 (delapan) orang informan yang dilakukan secara snowball. Pengumpulan data dilakukan dengan wawancara, observasi dan dokumentasi. Hasil penelitian yang pertama mengungkapkan bawah pandemic COVID-19 dimaknai secara personal membuat ketakutan dan memunculkan berbagai macam kecemasan hingga berdampak pada fisik dan mental seseorang. Sehingga perlu adanya upaya pencegahan yang dilakukan agar virus ini tidak semakin menyebar. Disisi lain kecemasan yang berlebihan hingga memunculkan keluhan fisik membuat seseorang mengalami psikosomatik. Gejala psikosomatik dapat berupa gejala mental seperti stress hingga menimbulkan gejala fisik seperti munculnya keluhan ditubuh yang ketika dilakukan pengecekan tidak terdapat disfungsi pada bagian tubuh tersebut. Psikosomatik yang dialami seseorang dapat menjadi penghambat seseorang dalam berkomunikasi. Seseorang yang mengalami psikosomatik hingga yang parah sehingga mengganggu aktivitas sehari-hari perlu melakukan pengobatan dengan mendatangi tenaga professional baik psikolog atau psikiater. Temuan terakhir yang peneliti peroleh dari efek setelah adanya komunikasi terapeutik yang terjalin penyintas menjadi sadar pentingnya berkonsultasi dengan tenaga professional untuk memperoleh kelegaan sehingga ia dapat beraktivitas kembali secara normal. Dari hasil penelitian peneliti menyimpulkan bahwa kecemasan yang dialami seseorang dapat membuat daya tahan tubuhnya melemah sehingga menyebabkan penyakit fisik. Ketika kecemasan sudah berdampak pada aktivitas sehari-hari maka masyarakat perlu mendatangi tenaga professional untuk memperoleh pengobatan sehingga dampaknya tidak semakin berat.